The effect of cracks on the bearing capacity of masonry structures - Popok, Karina (Lira-K, 2016)
The research of the effect of different types of cracks in the elements on their bearing capacity according to the calculations by past and current codes – Building Regulations ІІ22-81 (SNiP ІІ-22-81) and State Building Codes of Ukraine V.2.6-162:2010 (DBN V.2.6- 162:2010) respectively, has been conducted. The effect of the three types of cracks in the masonry structures – through vertical (single, not the compressive overload ones), through horizontal and inclined ones along indents on the bearing capacity of masonry has been analyzed. The paper provides the numerical example in which the bearing capacity of the masonry pier in the initial state (before cracking) and after cracking has been analyzed according to the calculations by the above codes.
Keywords: masonry structures; cracks; bearing capacity; central and eccentric compression; principal tensile stresses; 624.012.1:620.191